ANALYSIS OF LOCUTION AND ILLOCUTIONAL SPEECH ACTS ON THE SELF-DEVELOPMENT PLAYLIST FOUND IN YOUTUBE CHANNEL OF SI KUTU BUKU - Rizky Candra Satria; Areta Etsa Faustina; Liza Asri Ariana; Putrinanda Denisa Azhary; Asep Purwo Yudi Utomo (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This research is motivated by the increasingly widespread media technology, especially on Youtube media, where each video is able to convey information with various purposes in each of its speeches. This study aims to deepen and broaden knowledge regarding speech acts, as well as explain locutionary and illocutionary speech acts contained in the Self-Development videos on the Bookworm Youtube Channel. Qualitative descriptive methods, pragmatic approaches, listening techniques, and note-taking techniques form the basis of this research. Based on the analysis of locutionary and illocutionary speech acts in the Self-Development playlist on The Nerdy Youtube Channel, the utterances here contain several meanings related to speech events and speech acts which are the material in the analysis. So from several videos on the Youtube Channel that have been collected and researched using locutionary and illocutionary speech acts, the researcher found 3 types of locutionary speech, which include declarative, interrogative, and imperative speech. As well as 3 types of illocutionary speech which include assertive, directive, and commissive speech. We hope that this research will bring renewal and complement the results of other pragmatic studies, especially those related to locutionary and illocutionary speech acts.